Assessment of injection moulded parts of PP/nanoclay produced with hybrid moulds - Neves, A. F. (2013)
The concept of hybrid mould combines the conventional techniques of mould manufacturing and Rapid Prototyping and Rapid Tooling, resorting to non-conventional materials for producing moulding blocks, e. g., epoxy resin composites. Composites based on an epoxy system with 15% weight fraction of short steel fibres (SSF) were considered adequate for improving the performance of moulding blocks. The epoxy/short steel fibre composite moulding blocks were produced by vacuum casting in silicone moulds. Polypropylene (PP) was mixed with a commercial PP masterbatch with 50% of nanoclay and injected in a hybrid mould under various processing conditions. These were chosen from a central composite design with 15 experiments. The moulding microstructure was assessed by polarized light microscopy and differential scanning calorimetry. The skin-core morphology was observed and suggested that the low thermal conductivity of the epoxy composite produces a thinner skin when compared to all-steel moulds. The nanoclay concentration was the variable with the most significant effect on skin thickness and crystallinity. The addition of 1 wt% nanoclay under certain processing conditions favours the formation of β-form spherulites and the increase of crystallinity.